Implementation Of Rapid Application Development Methodology In UI/UX Design of Mangrove Forest Information System - Supiyandi, Supiyandi; Rizal, Chairul; Hermansyah, Hermansyah; Khodijah, Siti (Journal of Information System Research (JOSH), 2024)
Concentrates on utilizing the Rapid Application Development (RAD) approach to improve the User Interface (UI) and User Experience (UX) of an information system designed for mangrove forest conservation. Mangrove ecosystems are essential for coastal defense, biodiversity, and carbon storage. Nonetheless, insufficient access to information frequently impeded community involvement in mangrove conservation. The research tackles this deficiency by creating a user-centric information system that amalgamates environmental data, cartographic representations, and educational materials concerning the mangroves of Desa Kota Pari. RAD was selected for its iterative and adaptable characteristics, facilitating ongoing stakeholder feedback and expedited development cycles relative to conventional models. The study delineates a multi-phase Rapid Application Development (RAD) methodology, encompassing requirements elicitation, prototyping, and user evaluation to develop a functioning and user-friendly system. By engaging end-users, including local authorities, conservationists, and community members during the development process, the system's UI/UX was tailored to address the distinct requirements of its audience, facilitating usability and the clear conveyance of intricate ecological data. Preliminary responses from usability assessments indicated a notable enhancement in user engagement and comprehension of mangrove conservation initiatives. The Mangrove Forest Information System demonstrates that the RAD technique is highly effective in developing interactive and user-centric environmental information systems, particularly in contexts requiring swift adaptation to user requirements. This approach improves community involvement and supports the sustainability of mangrove ecosystems.